Mechanical and physical properties of highly eggshell-filled Bis-GMA/TEGDMA for dental application / Muhammad Syakir Ikhwan Saddun Zuber … [et al.] - Saddun Zuber, Muhammad Syakir Ikhwan; Aziz, Nora; Azlisham, Nor Ain Fatihah; Johari, Yanti; Abdullah, Abdul Manaf (Universiti Teknologi MARA Shah Alam, 2022)
This study attempts to assess a newly developed eggshell-filled Bisphenol A-glycidyl methacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) for dental application. Amounts of 30 and 40 wt% of eggshell were filled in Bis-GMA/TEGDMA along with 1% of benzoyl peroxide, followed by the fabrication of rectangular specimens of 20 × 25 × 2 mm for evaluation of physical and mechanical properties. Prior to the fabrication of the composites, the morphology of the eggshell was observed using a field emission scanning electron microscope. The surface roughness and hardness of the specimens were assessed using a surface profilometer and Vickers hardness tester, respectively. The eggshells were irregular in shape with sizes ranging between 5 to 60 µm. The roughness values slightly fluctuated with the incorporation of fillers. The roughest surface was recorded by 40 wt% filled Bis-GMA/TEGDMA with 1.34 µm. On the contrary, the hardness of the composites increased by 37 to 73% as compared to the unfilled Bis-GMA/TEGDMA. With improved mechanical performance as well as physical characteristics that could be further enhanced, eggshell-filled Bis-GMA/TEGDMA could be the next potential substitute for sustainable dental materials, subjected to further investigations.